PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN KOPERASI KARYAWAN SEJAHTERA UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Yuliana, Eka; Miftahudin, Muchammad Agung (Media Ekonomi, 2015)
This research aimed analyze the independent variable effect (tangibles, reliability, responsiveness, assurance, and empathy) towards the dependent variable (consumers satisfactory) in Koperasi Karyawan Sejahtera University of Muhammadiyah Purwokerto.In this research, the researcher did the sampling by distributing questionnaire. The total of sample was 120 respondents. The analysis don was by double regression analysis.The t test showed that the independent variable of tangibles, reliability, responsiveness, assurance, and empathy affected partially towards the dependent variable consumers’ satisfactory, while the variable of reliabilty and responsiveness did not affect on consumers’ satisfactory in a whole. Based on the elasticity test, the variable of tangibles affected dominantly toward consumers’ satisfactory.Keywords: tangibles, reliability, responsiveness, assurance, and empathy, consumers’ satisfactory